KNOWLEDGE AND PERCEPTION OF NEW GRADUATES ON TREATING PATIENTS WITH SPECIAL NEEDS IN DENTISTRY: AN ORIGINAL RESEARCH (Journal of Pharmaceutical Negative Results, 2023)
Aim: The purpose of the present research was to assess the knowledge, perception of new dental graduates about treating specially abled patients.Methodology: A cross‑sectional study was conducted among a conveniently sampled 45 new dental professionals from the same institution who were both private dental practitioners. Participants were interviewed through a validated questionnaire, which consisted of 14 items. The questionnaire comprised demographic details of the participants, their years of dental experience, disabled patients they had encountered so far in their practice, and questions related to their attitude, perception, and practice to provide oral health care for patients with special needs. Informed consent was obtained from the participants prior to the study. The data obtained were entered into Microsoft Excel 2010 and descriptive statistics was computed using the SPSS Statistics for Windows, Version 25.0. Armonk, NY: IBM Corp.Results: A response of 71% was obtained. Majority of the dentists (65%) were unaware of the Right to Disability Act. Half of the dentists (50%) felt teledentistry would do more good to people with special needs. About (31.8%) of them felt inadequate training to handle patients with special needs as major barrier faced while treating them.Conclusion: Majority of the study participants felt inadequate training among the dental practitioners as barrier to treat special needs patients and hence suggested incorporation of special care dentistry into the dental curriculum.